THE EFFECT OF ORGANIZATIONAL CULTURE TOWARDS ORGANIZATIONAL PERFORMANCE CASE STUDY : DINAS PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI UTARA - Sengke, Gerald (Sam Ratulangi University, 2016)
ABSTRACT Culture have a big influence on organizations performance in the world-wide. Absolutly all the organizations have their own culture. The organizational culture like competitive culture, entrepreneurial culture, bureaucratic culture and consensual culture has an effect on organizational performance. The study aims to know the effect of the organizational culture towards organizational performance at Disperindag Sulut. 98 employees or the all the employees at Disperindag were surveyed as samples. The result show organizational culture has a great effect on organizational performance, consensual culture, competitive culture and bureaucratic culture have a significant effects on organizational performance. The employees on the Disperindag prefer to seek work environment that maximizes on their ability to be creative, innovative and work as a team with each other. While entrepreneurial culture is needs to be strengthened for the employee to become creative and innovative for the better performance. Keywords: Organizational culture, Organizational performance